Ghost Kitchens And The Digitalization Of Indonesia’s Urban Informal Economy - Susanto, Eko; Gaffar, Vanessa; Prawira, Mega Fitriani Adiwarna (Journal of Consumer Studies and Applied Marketing, 2025)
Ghost kitchens have emerged as a disruptive force in Indonesia’s urban food economy, driven by digitalization, platform-based business models, and changing consumer behaviour. By eliminating the need for physical storefronts, they enable small entrepreneurs to reduce operational costs and access a broader market through food delivery platforms like GoFood, GrabFood, and ShopeeFood. However, their reliance on these platforms creates new economic dependencies, as algorithm-driven visibility and commission fees significantly impact profitability. Additionally, the rise of ghost kitchens intensifies market competition, particularly between independent operators and corporate-backed cloud kitchens that dominate rankings and resources. This study employs a qualitative multiple-case study approach to examine the economic and regulatory implications of ghost kitchens, including their impact on traditional food vendors, gig workers, and urban policies. Findings reveal that while ghost kitchens increase business accessibility, they also contribute to labour precarity within the gig economy, as food delivery workers face unstable incomes and high operational costs. The study underscores the need for adaptive regulatory frameworks, including fair taxation, food safety measures, and platform accountability to ensure equitable market participation. As ghost kitchens continue to evolve, proactive policies are required to balance innovation with sustainability, ensuring long-term benefits for entrepreneurs, workers, and consumers in Indonesia’s digital food ecosystem.